What is Québécois Literature? Reflections on the Literary History of Francophone Writing in Canada - Chapman, Rosemary (Contemporary French and Francophone Cultures, 2013)
The question 'What is Québécois literature?' may seem innocent and answerable, yet Rosemary Chapman's compelling study shows that to answer it is to chart the cultural history of French Canada, to put francophone writing in Canada in postcolonial context and to ask whether literary history, with its focus on the nation, is in fact obsolete.This remarkable book will be compulsory reading for scholars well-versed in francophone postcolonial studies and will also act as an ideal introduction for Anglophone scholars of Canadian literature.